Comparative Studies between T-Junction and Rotary Junction and Alternate Method to Minimize the Traffic Flow (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As we all know that the situation of traffic flow in metropolitan cities is getting deteriorated day by day, Traffic management is the only key for the having better results. Our study now deals with a similar kind of issue; the study area which was taken is a stretch between the two T- junctions which lies in the vicinity of the IT corridor Hyderabad, Telangana. The study deals with traffic flow counting, analyzing the peak hour volume, designing signals for the junctions, creating a model in VISSIM Software and trying to understand the delays. As an alternate arrangement the T-junctions are replaced with U-turns and it will be analyzed and since the data we have received meets the need for a Rotary too, the signals are being taken away amidst the stretch and is replaced by a rotary. The main objective of our study is to make comparative studies between the junction when replaced with U-turn and Rotary. Our study tries to suggest a way to reduce on the delays caused by the vehicles in the junction which in return paves a way for sustainable urban cities.